Love makes a family - Beer, Sophie (New York, NY : Dial Books for Young Readers, 2018)
Celebrates the love that members of many different types of families have for each other.
Keywords: Board books; Family life -- Fiction; Love -- Fiction; Board books; Family life -- Fiction; Love -- Fiction; Board books for children